Can Yoga Boost Access to the Bodily and Emotional Self? Changes in Heart Rate Variability and in Affective Evaluation Before, During and After a Single Session of Yoga Exercise With and Without Instructions of Controlled Breathing and Mindful Body Awareness in Young Healthy Women - Herbert, Cornelia (Frontiers in Psychology, 2021)
Exercise is indispensable for a healthy lifestyle. Yoga exercise can have positive effects on well-being and on cardiac autonomous functioning making it an ideal intervention for improving mind-body interactions and resilience to physical and mental stressors. Emotions trigger especially strong bodily and affective-cognitive responses because of their social relevance for the self and their biological relevance of mobilizing the organism for action. This study investigates whether changes in emotion processing related to self-other referential processing and cardiac autonomic functioning, reflected by heart rate variability (HRV), occur immediately after already a single session of yoga exercise when yoga postures are practiced with or without breathing and mindfulness body awareness instructions. Women, all university students (N=34, final sample: n=30, n=25 naïve to yoga practice) were randomly assigned to two experimental groups who performed the same yoga exercises with or without controlled breathing and mindfulness instructions. Emotional, self-referential processing, awareness of bodily signals and HRV indicators were investigated before and after the exercise using standardized experimental tasks, standardized questionnaires, and mobile recording devices. Exercising yoga for 30 minutes changed cardiac activity significantly. HRV measures showed adaptability of cardiac activity during the exercise as well as during the affective task post- to pre-exercise. Exercising with breathing instructions and mindfulness body awareness had no superior effects on cardiac, particularly parasympathetic activity compared to practicing the same movements without such explicit instructions. Self-referential processing did not change; however, participants were faster and more accurate in their affective judgments of emotional stimuli (regardless of their reference (self/other)), and showed better awareness of bodily signals after compared to before the exercise session. The results support immediate, adaptive effects of yoga exercise on cardiac and affective-cognitive processing in an all-female healthy sample supporting yoga as an exercise for boosting cardiac and emotional resilience in this target group.